2018
DOI: 10.1063/1.5020443
|View full text |Cite
|
Sign up to set email alerts
|

Ambipolar transport in CVD grown MoSe2 monolayer using an ionic liquid gel gate dielectric

Abstract: CVD grown MoSe2 monolayers were electrically characterized at room temperature in a field effect transistor (FET) configuration using an ionic liquid (IL) as the gate dielectric. During the growth, instead of using MoO3 powder, ammonium heptamolybdate was used for better Mo control of the source and sodium cholate added for lager MoSe2 growth areas. In addition, a high specific capacitance (∼7 μF/cm2) IL was used as the gate dielectric to significantly reduce the operating voltage. The device exhibited ambipol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 23 publications
3
11
0
Order By: Relevance
“…Our AlO x -capped 2L devices achieve a record-high current density for atomically thin MoSe 2 of ∼65 μA/μm, with an I on / I off > 10 6 and R C of ∼60 kΩ·μm. 30 , 34 , 38 40 These results represent ∼20× improvement in R C and ∼30× enhanced current density compared to our (AlO x -capped) 1L devices. The AlO x doping effect aligns well with previously reported data for 1L and FL MoS 2 and ReS 2 encapsulation.…”
Section: Introductionsupporting
confidence: 49%
“…Our AlO x -capped 2L devices achieve a record-high current density for atomically thin MoSe 2 of ∼65 μA/μm, with an I on / I off > 10 6 and R C of ∼60 kΩ·μm. 30 , 34 , 38 40 These results represent ∼20× improvement in R C and ∼30× enhanced current density compared to our (AlO x -capped) 1L devices. The AlO x doping effect aligns well with previously reported data for 1L and FL MoS 2 and ReS 2 encapsulation.…”
Section: Introductionsupporting
confidence: 49%
“…However, during the synthesis process of MoSe 2 via chemical vapor transport (CVT) or chemical vapor deposition (CVD), uncontrolled defects states can be introduced in the MoSe 2 flakes, because of involving the high temperature and pressure environment to produce a single crystal mineral TMD. Therefore, the synthesized MoSe 2 FETs tend to randomly exhibit the characteristics of not only n‐type behavior but also ambipolar or p‐type behavior; as shown in previous results, it has been reported that CVD‐ or CVT‐grown MoSe 2 FETs can be ambipolar, n‐dominant, or p‐dominant transistors depending on the growth conditions. To enable the integration of CVD‐ or CVT‐synthesized MoSe 2 in practical devices, these inhomogeneous characteristics of MoSe 2 FETs should be unipolar.…”
supporting
confidence: 58%
“…When the thickness of MoSe 2 continuously increased to about 7 layers, the transistor showed ambipolar behaviors . Furthermore, monolayer MoSe 2 could realize ambipolar charge transport by employing EDL technique …”
Section: Inorganic Semiconducting Materialsmentioning
confidence: 99%